Impact of animated video media on enhancing numeracy skills among primary school students - Raudha, Azzura; Alim, Jesi Alexander; Fendrik, Muhammad (Al-Jabar: Jurnal Pendidikan Matematika, 2024)
Background: The low level of student participation in the learning process is often attributed to the use of methods that fail to engage students' interest. This issue underscores the need for innovative approaches in teaching to enhance student engagement, one of which involves the utilization of animated video media, which has the potential to create more engaging learning experiences.Aim: This study aims to explore and describe the impact of using animated video media as a learning tool on the numeracy skills of elementary school students.Method: This research adopts a quantitative approach, where the data collected is numerical and analyzed using statistical methods. The study population consisted of 48 students from an elementary school in the Lalang area, Sungai Apit District. The sample comprised 31 students, divided into two classes, selected through random sampling techniques. Data collection was conducted through direct observation in collaboration with the classroom teacher. Data analysis involved normality tests, homogeneity tests, and an independent sample T-test.Result: The findings of this study indicate an improvement in students' numeracy skills through the use of animated video media. This improvement is evident from the comparison of pretest and posttest scores, where the experimental class demonstrated an increase of 28.67 compared to the control class.Conclusion: The use of animated videos positively impacts mathematics learning outcomes and contributes to enhancing the numeracy skills of elementary school students.